Development of Learning Application for Topic Circular Measure for Additional Mathematics Form 5 - Hamzah, Norhasyimah; Mahmood, Marwa; Zakaria, Normah; Ariffin, Arihasnida; Rubani, Siti Nur Kamariah (Research and Innovation in Technical and Vocational Education and Training, 2024)
Additional Mathematics is an elective subject in high school. However, students' scores in this subject are among the lowest in the most recent SPM exam results. This is one of the factors that makes Additional Mathematics an unsatisfactory subject. This study aims to develop a Learning Application for the Topic of Circular Measure for Additional Mathematics Form 5, considering that Additional Mathematics is an SPM subject where students' results have been unsatisfactory in recent years. The developers have used Hannafin and Peck's model throughout the development process of this learning Android app.  In addition, two types of instruments have been used in this project which are checklist form and verification expert. The checklist form is used for expert assessment for the development of learning android applications. Three (3) experts evaluate the functionality of the developed learning Android application. The findings show that expert evaluation is based on aspects of content design, interface design, and interaction design by the standards for developing learning Android applications. Overall, the development of learning android applications for the topic of circular measure for Additional Mathematics subjects Form 5 can be one of the teaching aids in teaching and learning at school.